Development of a compact continuous-flow electrochemical cell for an energy efficient production of alkali. (20th October 2015) - Mehmood, Asad; Jang, Eunjin; Lee, Nakwon; Jung, Kwang-Deog; Ha, Heung Yong
Highlights: A compact electrochemical cell is developed to electrolyze brine into NaOH and HCl. Two cell structures have been compared for producing alkali with low energy input. The performance of the cell is affected by the thickness of the middle plate. Structural modifications of the anode allow a 75% reduction of Pt loadings. Pt black as a cathode catalyst shows a better performance stability than Pt/C. Abstract: In this study, we report development of a compact continuous-flow electrochemical cell for an energy-efficient splitting of brine (aqueous NaCl) to yield alkali (NaOH) that would be used for sequestration of carbon dioxide into carbonate minerals at a subsequent stage. Herein, at the first step of process development, cell design and electrode structures are optimized for producing NaOH with minimum input energy. Two cell designs representing a primitive version (design 1) and an advanced version (design 2) are evaluated. The advanced structure of electrochemical cell with a thinner middle compartment exhibits up to 300% improvement in output current density as compared to the primitive version due to shorter ionic diffusion paths. Structural modifications of the anode lead to a successful reduction of Pt loadings by an appreciable amount of 75% without compromising the cell performance. Pt black as a cathode catalyst shows a significantly better performance stability as compared to Pt/C, which experiences a sharp performance decline in a 50 h steady-state operation. It has been demonstrated that the compact structure of electrochemical cell allows use of a highly diluted NaOH solution (0.1 M) as catholyte without deteriorating the cell performance and stability. Finally, caustic efficiency and different figures of merit are calculated.